Situation Report: Czechoslovakia, 20 November 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Czech Writers: After the Stick a Carrot? A Hardliner Reconsiders Federal Socialist Youth Union Constituted Exiles on Trial Increase in Alcohol and Tobacco Consumption Command Performance